Pengaruh Konsumsi Jus Buah Naga Terhadap Kadar Hemoglobin (Hb) pada Ibu Hamil Di Dusun Olas - Syahfitrah Umamity; Siti Rochmaedah; Trysna Ayu Sukardi; Maryati Mardjuky (Universitas Pahlawan Tuanku Tambusai, 2025)
Pregnant women are said to have anemia if the mother's hemoglobin level is less than 11g/dl in the first and third trimester, and less than 10.5 g/dl in the second trimester. Anemia also has an impact on the development of children and mothers, handling anemia in pregnant women is very important to overcome. Non-pharmacologically with complementary therapy, one of which is a type of complementary therapy by consuming fruit, for example consuming dragon fruit. The purpose of the study was to determine the effect of dragon fruit juice consumption on Hemaglobin (Hb) levels in pregnant women in Olas Hamlet. This research uses a quantitative method with a quasi-experimental design research type with a one-group pre-test and post-test design. The population of this study is all pregnant women in Olas Hamlet as many as 20 people. The instruments in the study were SOPs for administering dragon fruit juice and observation sheets for hemoglobin levels before and after treatment. The results show that the Wilcoxon sig rank test statistical test shows a value of sig = 0.001 < α = 0.050, this means that H0 is rejected and H1 is accepted, so it can be interpreted that the results of the Wilcoxon test on the Hb post and Hb pre levels score show that there is an influence on the administration of dragon fruit juice to pregnant women. Conclusion there is an effect of dragon fruit juice consumption on Hemoglobin levels of pregnant women. Keywords: red dragon fruit juice; Hemoglobin levels; Pregnant women